Temozolomide duration and secondary hematological neoplasms: A literature review and implications for patients with neuroendocrine neoplasms. (19th July 2022) - Park, Robin; Amin, Manik; Trikalinos, Nikolaos A.
Abstract: Evidence‐based recommendations for the optimal duration and sequencing of temozolomide‐based treatments in advanced neuroendocrine neoplasms are lacking. Here, we conducted a systematic review of the literature for a descriptive analysis of temozolomide‐associated myelodysplasias and leukemias to guide treatment planning. A database search of PubMed and Embase was conducted to identify case reports and/or case series reporting secondary myelodysplasias or leukemias in the setting of temozolomide therapy. Key data items extracted from the studies were the temozolomide dose and duration, latency to hematological disorder, type of secondary malignancy and cytogenetics. Reported cases were summarized graphically. A total of 16 studies with 27 patient cases of therapy‐related hematologic neoplasms were identified, all of which were case reports or case series. The median treatment duration and cumulative dose were 19 months and 18, 000 mg/m 2, respectively. Most patients (21/27) were diagnosed on, or after, 12 months, while only one patient was diagnosed before 6 months of treatment. Most of the patients were diagnosed, while still on treatment with temozolomide. Graphically, cases clustered around a cumulative dose of 10, 000 to 30, 000 mg/m 2 and a latency period of 10 to 40 months which translates to an approximate treatment duration of 12.5 to 37.5 months. Taken together, most reported treatment‐related hematological neoplasms appear to develop on or beyond the 12‐month mark, while patients are still on treatment with temozolomide. For patients with neuroendocrine neoplasms, where sequencing of multiple therapies is important, we suggest an approach to optimizing treatment duration by establishing disease response at 6 months before continuing further treatment and restricting treatment to or establishing closer vigilance beyond 12 months. Abstract : Capecitabine and temozolomide (CAPTEM) has established efficacy in advanced neuroendocrine neoplasms (NEN). Unlike in patients with primary neoplasms of the brain, where temozolomide is also commonly used, patients with NEN have a much longer expected overall survival and consequently may be exposed to longer durations of temozolomide which is typically given until unacceptable toxicity, disease progression, or death. While relatively well tolerated, especially with regards to acute toxicity, temozolomide is associated with cumulative risk of therapy‐related hematologic toxicity including therapy‐related leukemias, which is particularly relevant given the potential prolonged exposure. Here, we review the literature to help inform the optimal duration of temozolomide therapy taking into context the risk of long‐term therapy‐related hematologic toxicity.